Enhancement of heavy metal immobilization in sewage sludge biochar by combining alkaline hydrothermal treatment and pyrolysis. (1st October 2022) - Li, Chunxing; Li, Jie; Xie, Shengyu; Zhang, Guangyi; Pan, Lanjia; Wang, Ruming; Wang, Gang; Pan, Xiaofang; Wang, Yin; Angelidaki, Irini
Abstract: Heavy metals, including Cd, As, Ni, Cu, Pb, Cr, Zn, and Mn in sewage sludge (SS) are among the greatest impediments to SS application because of their potential toxicity to living organisms and latent environmental pollution risks. In this study, hydrothermal treatment (HT)/alkaline HT combined with pyrolysis was used to treat SS for heavy metal immobilization. The heavy metal characteristics, including total, fraction, and leaching concentrations and potential ecological risks, were comprehensively investigated to ensure the safe application of biochar. The results showed that the heavy metals mainly remained in the hydrochar and biochar. Additionally, both HT and alkaline HT promoted the residual fractions of Cr, Zn, Ni, and Cu in biochar. Furthermore, alkaline HT-aided pyrolysis was more effective for immobilizing Zn and Ni with their residual fractions increasing by 100% and 60% respectively, compared with direct sludge pyrolysis. Moreover, the ecological risk of heavy metals in SS significantly decreased from 57.27 to 30.05 after alkaline HT-combined pyrolysis treatment, contributing to the low potential ecological risk of SS-based biochar. This study provides a promising strategy for converting SS to biochar with improved heavy metal immobilization. Graphical abstract: Image 1 Highlights: Alkaline hydrothermal treatment combining pyrolysis was used to treat sewage sludge. Heavy metals mainly remained in the hydrochar and biochar after treatment. Adding alkaline further contributed to the heavy metal immobilization. F4 of Zn and Ni increased by 100% and 60% after alkaline aided pyrolysis. Alkaline aided pyrolysis led to lower potential ecological risk of heavy metal.